Front Cover: One‐Step Direct Synthesis of SiO2–TiO2 Composite Nanoparticle Assemblies with Hollow Spherical Morphology (Eur. J. Inorg. Chem. 24/2017). Issue 24 (17th May 2017) - Nguyen, Hien Thi Thu; Habu, Teppei; Ohtani, Masataka; Kobiro, Kazuya
Abstract : The cover picture shows the SiO2 –TiO2 composite MARIMO assemblies with and without alkyl groups synthesized directly by simple, one‐step, and one‐pot solvothermal reactions of Si alkoxides and a Ti alkoxide. A uniform spherical morphology with a porous shell and cavity was obtained. Properties such as the diameter and cavity size of these assemblies can be controlled by adjusting the ratio of the Si and Ti alkoxides in the precursor solutions, by adding a second acid, and by changing the reaction temperature. Details are discussed in the article by M. Ohtani, K. Kobiro et al. on page 3017 ff (https://doi.org/10.1002/ejic.201700253 ). For more on the story behind the cover research, see the Cover Profile (https://doi.org/10.1002/ejic.201700522 ).